Protein and starch sources varying in rumen degradability to feed dairy cows - Imaizumi, Hugo; Santos, Flávio Augusto Portela; Pires, Alexandre Vaz; Juchem, Sérgio de Oliveira (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate starch sources (fine ground x popped corn) and protein sources (soybean meal x fish meal x urea) varying in rumen degradability in order to feed dairy cows. Fifty-six Holstein cows averaging 112 days in milk were used. The treatments were: MFS (fine ground corn + soybean meal); PFS (popped corn + soybean meal); PFP (popped corn + soybean meal + fishmeal) and PU (popped corn + soybean meal + urea). The treatment PFS did not affect milk yield, but it decreased milk fat content, milk fat yield and milk protein content, compared to MFS. Milk yield was higher for PFS than for PFP or PU. Treatment with fishmeal (PFP) decreased milk fat content, milk fat yield and 3.5% FCM yield, but increased milk protein content.